Marshall McLuhan’s Counterenvironment within the Stream of Defamiliarization (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract: Marshall McLuhan’s theory of the counterenvironment is within a larger tradition of defamiliarization that emerges in Romanticism and can be further traced through the writings of Henri Bergson, English literary modernism, Russian formalist ostranenie, Brechtian estrangement, and more recent institutional critique. Among related Romantic writings, Percy Bysshe Shelley’s essay “A Defence of Poetry” (1821) clearly anticipates later theories that both repeat and develop fundamental notions of defamiliarization. Bergson’s writings on the comic revive Romantic ideas when he states that the object of the arts is “to brush aside the utilitarian symbols, the conventional and socially accepted generalities, in short, everything that veils reality from us, in order to bring us face to face with reality itself.” English modernists such as T.E. Hulme, T.S. Eliot, and their contemporaries drew on Bergson and were major sources for McLuhan’s counterenvironment. Russian formalist and English modernist defamiliarization share roots in Romanticism and Bergson, which account for their sometimes parallel perspectives. McLuhan had some limited exposure to Russian formalism by way of Constructivist cinema as well as the art and writings of László Moholy-Nagy. Later writers sometimes mistakenly view Viktor Shklovsky’s ostranenie to be at the origin of defamiliarization, although it was a point of departure for Bertolt Brecht’s “alienation effect.” McLuhan began using the term counterenvironment not long before some artists (who were aware of McLuhan’s writing on the subject) started to direct the audience’s aestheticized attention to the situation’s contextual framework rather than to discrete objects alone. Like the counterenvironment, later institutional critique proposed a Gestalt reversal of attention by turning the environmental ground to figure, thereby prompting awareness of what had been earlier ignored. McLuhan’s theory of the counterenvironment, and the variations of defamiliarization more generally, are historically specific while also partaking in transformative historical processes that involve a fusion of communication, change, continuity, and repetition.Résumé | La théorie du contre-environnement de Marshall McLuhan s’inscrit dans une perspective plus large de défamiliarisation qui a vu le jour dans le romantisme et peut être retrouvée dans les écrits d’Henri Bergson, la littérature moderniste anglaise, le formalisme russe, la distanciation brechtienne, et la critique institutionnelle plus récente. Parmi les écrits romantiques apparentés, l’essai de Percy Bysshe Shelley, « A Defense of Poetry » (1821) anticipe clairement des théories ultérieures qui à la fois répètent et développent des notions fondamentales de défamiliarisation. Les écrits de Bergson sur la bande dessinée font revivre les idées romantiques quand il déclare que l’objet des arts est de « mettre de côté les symboles utilitaires, les généralités conventionnelles et socialement acceptées, bref tout ce qui voile la réalité, pour nous mettre devant la réalité elle-même ». Des modernistes anglais tels que T.E Hulme, T.S. Eliot, et leurs contemporains, se sont inspirés de Bergson et ont été des sources importantes pour le contre-environnement de McLuhan. La défamiliarisation du formalisme russe et du modernisme anglais tirent leur origine du romantisme et de Bergson, ce qui explique leurs perspectives parfois parallèles. McLuhan a eu une exposition limitée au formalisme russe à travers le cinéma constructiviste ainsi que l’art et les écrits de László Moholy-Nagy. Les auteurs ultérieurs considèrent parfois erronément l’ostranenie de Viktor Shklovsky comme étant à l’origine de la « défamiliarisation », bien que ce soit un point de départ pour « l’effet de distanciation » de Bertolt Brecht. McLuhan a commencé à utiliser le terme contre-environnement peu de temps avant que certains artistes, qui étaient au courant des écrits de McLuhan sur le sujet, commencent à diriger l’attention esthétisée du public sur le cadre contextuel de la situation plutôt que seulement sur des objets distincts. À l’instar du contre-environnement, la critique institutionnelle ultérieure a proposé un changement de direction de l’attention gestaltiste en transformant l’environnement en figure, suscitant ainsi la prise de conscience de ce qui avait été auparavant ignoré. La théorie de McLuhan du contre-environnement, et plus généralement les variations de la défamiliarisation, sont historiquement spécifiques tout en participant à des processus historiques de transformation qui impliquent une fusion de la communication, du changement, de la continuité, et de la répétition.: